2019
DOI: 10.1096/fj.201901569r
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe ameliorates lipid accumulation during adipogenesis by regulating the AMPK–mTORC1 pathway

Abstract: Adipogenesis, a critical process that converts adipocyte precursors into adipocytes, is considered a potential therapeutic target for the treatment of obesity. Ezetimibe, a drug approved by the United States Food and Drug Administration, is used for the treatment of hypercholesterolemia. Recently, it was reported to ameliorate high fat diet‐induced dyslipidemia in mice and reduce lipid accumulation in hepatocytes through the activation of AMPK. However, the anti‐adipogenic effects of ezetimibe and the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In livestock, the development of fat and muscle plays an important role in the formation of beef [ 17 ]. The process of preadipocyte proliferation and differentiation is the process of lipid accumulation [ 18 ]. This differentiation is the result of the synergistic effect of crucial transcription factors, especially PPARγ and C/EBPα [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In livestock, the development of fat and muscle plays an important role in the formation of beef [ 17 ]. The process of preadipocyte proliferation and differentiation is the process of lipid accumulation [ 18 ]. This differentiation is the result of the synergistic effect of crucial transcription factors, especially PPARγ and C/EBPα [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers screened the agents or intrinsic factors to inhibit mTORC1 signaling and lipogenesis for the treatment of obesity. Lee et al reported that ezetimibe reduced lipid accumulation by inhibiting mTORC1 signaling, leading to the downregulation of lipogenesis-related genes (23). Shi et al reported that the inhibition of miR-196b-5p blocked adipogenesis and lipogenesis by directly targeting TSC1 and TGFBR1 (transforming growth factor-b receptor 1) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al. reported that ezetimibe reduced lipid accumulation by inhibiting mTORC1 signaling, leading to the downregulation of lipogenesis-related genes ( 23 ). Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…49 Nevertheless, metformin may be a promising drug that could be further tested in TED patients. Additionally, ezetimibe, a cholesterol-lowering drug, activates AMPK and reduces lipid accumulation during adipogenesis, 50 and it may be useful in treating TED. Taken together, our study shows for the first time, to our knowledge, that miR-130a is elevated in human OFs prone to adipogenesis and promotes lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%